Zat Pengatur Tumbuh dan Pertumbuhan Bibit Karet (Hevea brasiliensis Muell.Arg) Asal Stum Mata Tidur - Ulfa Pratiwi dan; Ida Nursanti (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Sleeping eye stems are grafting seedlings whose grafting eyes have not yet grown. The advantage of using sleeping eye stems is that the preparation time is easier and faster, the price is relatively cheaper and it is easy to transport. Sleeping eye stems have a high percentage of mortality. To accelerate the growth of roots and shoots, sleeping eye stum grafting can be given growth regulators (ZPT). This study aims to determine the response of rubber seedlings to the provision of Growth Regulators with different concentrations on the growth of rubber seedlings from sleeping eye stum. This study used a completely randomized design (CRD) and the treatment design was Atonik with 4 treatment levels including; A0: Without ZPT Atonik, A1: ZPT Atonik 1 ml l-1 water, A2: ZPT Atonic 2 ml l-1, A3: ZPT Atonic 3 ml l-1, A4: ZPT Atonik 4 ml l-1. Data were analyzed using analysis of variance, followed by Duncan Multiple Range Test (DNMRT) at 5% α level. The results showed that the application of ZPT Atonik gave different responses to each growth of rubber seedlings of sleeping eye stum. Concentration of ZPT Atonik 1 ml l-1 and 2 ml l-1 gives the best effect on the growth of rubber seedlings (shoot length, number of leaves and dry weight of roots).